Glucose and its metabolites have distinct effects on the calcium-induced mitochondrial permeability transition - Skrha, J; Gáll, J; Buchal, R; Sedláčková, E; Pláteník, J (Folia biologica, 2011)
Mitochondrial production of reactive oxygen species (ROS) due to up-regulated glucose oxidation is thought to play a crucial, unifying role in the pathogenesis of chronic complications associated with diabetes mellitus. Mitochondrial permeability transition (MPT) is an interesting phenomenon involved in calcium signalling and cell death. We investigated the effects of glucose and several of its metabolites on calcium-induced MPT (measured as mitochondrial swelling) in isolated rat liver mitochondria. The presence of glucose, glucose 1-phosphate (both at 30 mM) or methylglyoxal (6 mM) significantly slowed calcium-induced mitochondrial swelling. Thirty mM glucose also resulted in a significant delay of MPT onset. In contrast, 30 mM fructose 6-phosphate accelerated swelling, whereas glucose 6-phosphate did not influence the MPT. The calcium binding potentials of the three hexose phosphates were tested and found similar. In vitro hydrogen peroxide production by mitochondria respiring on succinate in the presence of rotenone was independent of mitochondrial membrane potential and increased transiently during calcium-induced MPT. Inhibition of MPT with cyclosporine A resulted in decreased mitochondrial ROS production in response to calcium. In contrast, inhibition of MPT by methylglyoxal was accompanied by increased ROS production in response to calcium. In conclusion, we confirm that methylglyoxal is a potent inhibitor of MPT. In addition, high levels of glucose, glucose 1-phosphate and fructose 6-phosphate can also affect MPT. Methylglyoxal simultaneously inhibits MPT and increases mitochondrial ROS production in response to calcium. Our findings provide a novel context for the role of MPT in glucose sensing and the cellular toxicity caused by methylglyoxal.
Keywords: Calcium; reaktivní formy kyslíku; intracelulární membrány; permeabilita; Permeability; Mitochondria, Liver; vápník; krysa rodu Rattus; zvířata; glukosa; Reactive Oxygen Species; potkani Wistar; Pyruvaldehyde; jaterní mitochondrie; Intracellular Membranes; Rats, Wistar; Male; Glucose; Rats; Glucosephosphates; Animals; mužské pohlaví; pyruvaldehyd; glukosafosfáty